2021
DOI: 10.2298/tsci190404381g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of specific heat of aqueous graphene oxide Al2O3 hybrid nanofluid

Abstract: The specific heat of aqueous graphene+Al 2 O 3 (1:1) hybrid nanofluid was measured using the cooling method. The influence of nanoparticle mass fraction and temperature on the specific heat capacity of the hybrid nanofluids was investigated, the specific heat of the hybrid nanofluid was compared with that of aqueous graphene oxide nanofluid and Al 2 O 3 nanofluid. A fitted formula of the specific heat of the hybrid nanofluid was proposed based on the experimental data. It indicates that the specific heat reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The trend of variations in the SH of the nanofluids in different concentrations was similar to the base fluid since it is the main component of the nanofluid. Gao et al [64] experimentally investigated the SH of GO-Al 2 O 3 /water nanofluid and observed that a higher solid fraction caused more reduction in the SH. The highest reduction ratio in the SH was observed at the lowest temperature (20 • C) and the highest mass fraction of solids (0.15% wt), which was equal to 7%.…”
Section: Specific Heatmentioning
confidence: 99%
“…The trend of variations in the SH of the nanofluids in different concentrations was similar to the base fluid since it is the main component of the nanofluid. Gao et al [64] experimentally investigated the SH of GO-Al 2 O 3 /water nanofluid and observed that a higher solid fraction caused more reduction in the SH. The highest reduction ratio in the SH was observed at the lowest temperature (20 • C) and the highest mass fraction of solids (0.15% wt), which was equal to 7%.…”
Section: Specific Heatmentioning
confidence: 99%
“…They observed that the maximum reduction in specific heat capacity of nanofluid in comparison with the pure base fluid was around 30.12% in mixture ratio of 2:1. In another research, Gao et al [43] measured the specific heat capacity of a hybrid nanofluid, GO-Al 2 O 3 /water nanofluid for different concentrations and temperatures. They found that by increasing the concentration, the specific heat capacity of the nanofluid was decreased and this reduction was more noticeable at lower temperatures.…”
Section: Specific Heat Capacity Of Nanofluidsmentioning
confidence: 99%
“…Similar correlations have been proposed for hybrid nanofluids. For instance, Gao et al [43] proposed a correlation for specific heat capacity of GO-Al 2 O 3 /water by considering concentration and temperature as the inputs, which is:…”
Section: Specific Heat Capacity Of Nanofluidsmentioning
confidence: 99%
“…PV/T systems simultaneouslygenerate both electric andthermal energies using the same surface area.Several researchers have used air [4], water [5][6][7][8] and nanofluids to cool down PVs or reduce their surface temperatures by using a number of ways, including spraying water [9] and running a water film on the back surface of a PV with the help of nozzles [10]. Nanofluids are mixtures of phase-solid nanoparticles and deionized water, which are different as compared toconventional cooling fluids [11]. Nowadays, nanofluids have widespread applications and they have unique heat transfer characteristics, substantial thermal conductivity, and enhanced heat transfer mechanisms.…”
Section: Introductionmentioning
confidence: 99%